2022
DOI: 10.1016/j.gim.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in how women value risk-stratified breast screening

Abstract: Risk-stratified screening has potential to improve the cost effectiveness of national breast cancer screening programs. This study aimed to inform a socially acceptable and equitable implementation framework by determining what influences a woman's decision to accept a personalized breast cancer risk assessment and what the relative impact of these key determinants is. Methods: Multicriteria decision analysis was used to elicit the relative weights for 8 criteria that women reported influenced their decision. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Studies have also found hesitance amongst women to accept reduced surveillance, since they found regular screening reassuring [ 36 , 37 , 38 ]. Women integrate PBCRA with their own pre-existing health beliefs and notions of risk [ 39 ]. A systematic review found that low-risk PBCRA results did not necessarily reduce ‘perceived susceptibility’ amongst women [ 40 ], echoing concerns from GPs in the survey regarding public perception of removing screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also found hesitance amongst women to accept reduced surveillance, since they found regular screening reassuring [ 36 , 37 , 38 ]. Women integrate PBCRA with their own pre-existing health beliefs and notions of risk [ 39 ]. A systematic review found that low-risk PBCRA results did not necessarily reduce ‘perceived susceptibility’ amongst women [ 40 ], echoing concerns from GPs in the survey regarding public perception of removing screening.…”
Section: Discussionmentioning
confidence: 99%
“…Positive attitudes towards PBCRA relate to the value of results to inform decision making and deliver ‘result actionability’ [ 36 ]. In the majority of studies, PBCRA results are well-received by women at high risk [ 30 , 36 , 37 , 39 , 43 , 44 , 45 , 46 ], although one prospective study reported greater ‘genetic testing-specific distress’ and ‘decisional regret’ in women with a high PRS than in those with a low score [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, almost all germline cancer genetic testing in the NHS is done using blood samples. However, saliva is an equally good alternative for most testing and has the advantage of allowing the sample to be taken at home, making it more acceptable for women [ 47 ], and is more straightforward to transport. Incorporating breast density is more challenging in this age group as most women will not have had breast imaging.…”
Section: Test/intervention Principlesmentioning
confidence: 99%
“…Some suggested that a risk assessment could also be conducted or mentioned during cervical cancer screening appointments, but there were concerns about adding additional stress and/or anxiety to these already challenging healthcare appointments. There is also evidence that women prefer information by email or online rather than during GP consultations [ 47 ]. Research evaluating different implementation strategies and the impact on primary care and uptake is needed.…”
Section: Programme/system Principlesmentioning
confidence: 99%
“…16,17 However, for genetics to inform risk-based breast screening, how genetic testing is accessed was found to be more important than sensitivity and specificity of the risk assessment. 18 Although test sensitivity and mortality reduction are frequently the most important attributes of cancer screening programs to the public in general, 19 studies on risk stratification have focused on the risk factors themselves and not the potential impact on screening outcomes. No studies to our knowledge have explored the importance of such attributes relating to eligibility criteria, specifically, how accurate risk prediction models need to be to be acceptable when used to inform screening eligibility.…”
Section: Introductionmentioning
confidence: 99%